Evidence that a naturally occurring single nucleotide polymorphism in the RagC gene of Leishmania donovani contributes to reduced virulence - Lypaczewski, Patrick (PLoS Negl Trop Dis, 2021)
Leishmaniasis is a widespread neglected tropical disease transmitted by infected sand flies resulting in either benign cutaneous infection or fatal visceral disease. Leishmania donovani is the principal species responsible for visceral leishmaniasis, yet an atypical L. donovani has become attenuated in several countries including Sri Lanka and causes cutaneous leishmaniasis. Previous studies have identified 91 genes altered in the atypical cutaneous L. donovani compared to typical visceral disease associated L. donovani including mutations in the RagC and Raptor genes that are part of the eukaryotic conserved TOR pathway and its upstream sensing pathway. In the present study, we investigate whether the RagC R231C mutation present in atypical cutaneous L. donovani introduced into the virulent L. donovani 1S2D chromosome by CRISPR gene editing could affect virulence for survival in visceral organs. Through bioinformatic analysis, we further investigated the presence of sensing pathway components upstream of TOR in L. donovani including RagC complexing proteins, RagA and Raptor. L. donovani 1S2D edited to express mutant RagC R231C were viable in promastigote but had reduced visceral parasitemia in infected BALB/c mice. The RagC R231C mutant retained the ability to interact with RagA and gene knockout experiments revealed that although the RagA gene was essential, the RagC gene was not essential under promastigote culture conditions but was essential for survival in the liver of experimentally infected mice. These results provide evidence that the TOR associated sensing pathway plays a prominent role in L. donovani visceral disease and the RagC R231C mutation contributed to the atypical pathology of cutaneous L. donovani in Sri Lanka.